2011
DOI: 10.1007/s10822-011-9413-5
|View full text |Cite
|
Sign up to set email alerts
|

Transferable scoring function based on semiempirical quantum mechanical PM6-DH2 method: CDK2 with 15 structurally diverse inhibitors

Abstract: A semiempirical quantum mechanical PM6-DH2 method accurately covering the dispersion interaction and H-bonding was used to score fifteen structurally diverse CDK2 inhibitors. The geometries of all the complexes were taken from the X-ray structures and were reoptimised by the PM6-DH2 method in continuum water. The total scoring function was constructed as an estimate of the binding free energy, i.e., as a sum of the interaction enthalpy, interaction entropy and the corrections for the inhibitor desolvation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 84 publications
2
56
0
Order By: Relevance
“…[93] The best correlation with the experimental binding data was obtained when only the DE int and DDG solv terms were considered. CDK2 inhibitors were, however, less flexible and the corrections for the deformation and entropy played less important roles than in the case of HIV PR inhibitors.…”
Section: Applicationsmentioning
confidence: 92%
See 1 more Smart Citation
“…[93] The best correlation with the experimental binding data was obtained when only the DE int and DDG solv terms were considered. CDK2 inhibitors were, however, less flexible and the corrections for the deformation and entropy played less important roles than in the case of HIV PR inhibitors.…”
Section: Applicationsmentioning
confidence: 92%
“…[69,81,[92][93][94] In the first study, a series of HIV PR inhibitors were docked using UCSF DOCK and rescored by the PM6-DH2 scoring function. [69] The QM-based rescoring improved the docking results significantly (Figure 4 A,B).…”
Section: Applicationsmentioning
confidence: 99%
“…17,18,19 They also employ the more recent PM6 20 method with corrections for dispersion and hydrogen-bond interactions (DH2). 21,22 They use a single minimised structure of the complex, 3 although they have shown that energies calculated from a minimised structure of the ligand deviates by 13 kJ/mol on average from those calculated on an ensemble of structures from a MD simulation.…”
Section: = G(pl) -G(p) -G(l)mentioning
confidence: 99%
“…Future developments in these areas, coupled with an enhanced description of the physics underlying macromolecular interaction [232,[283][284][285][286][287][288][289][290][291][292][293][294][295][296], will be key for more predictive computational tools in structure-based drug discovery and design. Building the most reliable models is still based, and will probably always be, on the deep knowledge of the system or event under study.…”
Section: Discussionmentioning
confidence: 99%